1992
DOI: 10.1021/bi00152a043
|View full text |Cite
|
Sign up to set email alerts
|

DNA helicase E and DNA polymerase .epsilon. functionally interact for displacement synthesis

Abstract: A functional interaction between DNA helicase E and DNA polymerase epsilon from calf thymus has been detected which results in the extension of an upstream 3' OH through a downstream primer to the end of a synthetic template. DNA synthesis resulting in full-length extension products was dependent on the addition of DNA helicase E and hydrolysis of ATP, suggesting that displacement of the downstream primer was required. Identical reactions using DNA polymerases alpha and delta in place of DNA polymerase epsilon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Unlike HDH III, HDH II works somewhat more efficiently if the substrate has a 5' end tail as compared with a 3' end tail, suggesting that HDH II translocates in the 3' to 5' direction. By using the direction-specific substrate we confirmed that it moves in a 3' to 5' direction along the bound strand, like the previously described HDH I , HDH III (Tuteja et al, 1992), HDH V , DNA helicase a and DNA helicase £ from HeLa cells (Seo et al, 1991;Seo and Hurwitz, 1993), 47 kDa calf thymus DNA helicase (Thommes and Huibscher, 1990), calf thymus DNA helicase E (Turchi et al, 1992) and I (Zhang and Grosse, 1991), SV40 large-T antigen (Stahl and Knippers, 1987) and polyoma T-antigen (Seki et al, 1987).…”
Section: Discussionsupporting
confidence: 83%
“…Unlike HDH III, HDH II works somewhat more efficiently if the substrate has a 5' end tail as compared with a 3' end tail, suggesting that HDH II translocates in the 3' to 5' direction. By using the direction-specific substrate we confirmed that it moves in a 3' to 5' direction along the bound strand, like the previously described HDH I , HDH III (Tuteja et al, 1992), HDH V , DNA helicase a and DNA helicase £ from HeLa cells (Seo et al, 1991;Seo and Hurwitz, 1993), 47 kDa calf thymus DNA helicase (Thommes and Huibscher, 1990), calf thymus DNA helicase E (Turchi et al, 1992) and I (Zhang and Grosse, 1991), SV40 large-T antigen (Stahl and Knippers, 1987) and polyoma T-antigen (Seki et al, 1987).…”
Section: Discussionsupporting
confidence: 83%
“…No pausing is observed at ϩ2 for 3.5B and 4.5B, but the ϩ2 pause reappears in 5.5B, which suggests that the predicted helix melting may not occur until incorporation of the 3rd nucleotide in 5.5B rather than the predicted 2nd nucleotide. Regardless, more processive synthesis is observed through the ϩ5, ϩ6, and ϩ7 pause sites for substrates 5.5B, 6.5B, and 7.5B.…”
Section: Hiv-1 Rt Performs Limited Rna Displacement Synthesis On a Longmentioning
confidence: 92%
“…Not all DNA polymerases can perform displacement synthesis and often require accessory factors in the form of helicases and single-stranded DNA-binding proteins (5)(6)(7)(8)(9). Although retroviral nucleocapsid can enhance displacement synthesis, retroviral RTs have an intrinsic ability to synthesize DNA through duplex structures in the absence of other factors (10 -16).…”
mentioning
confidence: 99%
“…Our initial report on hel E demonstrated partial co-elution of pol c with hel E over the chromatographic matrices used during purification (4). These data suggest that hel E may form a loose physical complex with DNA pol e. Recent work from this laboratory has demonstrated a functional coordination between hel E and pol E resulting in DNA synthesis through a downstream primer dependent on helicase activity (10). The functional interaction with hel E was demonstrated to be specific for pol c. The results suggested that hel E may participate with pol E at the eukaryotic replication fork or in DNA repair.…”
Section: Introductionmentioning
confidence: 81%
“…at 37°C unless stated otherwise. Products were analyzed by 10% native polyacrylamide gel electrophoresis, and visualized by autoradiography as previously described (10).…”
Section: Enzymesmentioning
confidence: 99%